2011
DOI: 10.1159/000324297
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease-Specific Gene Expression Signatures of Alveolar Macrophages as well as Peripheral Blood Monocytes Overlap and Correlate with Lung Function

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease characterized by progressive airflow limitation and significant extrapulmonary (systemic) effects that lead to co-morbid conditions, though the pathomechanism of COPD is largely undetermined. Alveolar macrophages (AM) derived from peripheral monocytes (MO) appear to play a key role in initiating and/or sustaining disease progression. Objectives: To identify disease- and cell type-specific gene expression profiles and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 88 publications
(69 reference statements)
5
34
0
1
Order By: Relevance
“…Poliska et al found overlapping genes expressed in blood monocyte and alveolar macrophages in a limited number of COPD cases and controls. [70] Bhattacharya et al compared peripheral blood mononuclear cell expression profiles to their previous study of lung tissue,[16] finding several genes with similar expression results across the two tissues. [71] The lung-blood expression relationships found in the latter two studies show that peripheral blood can be used for COPD genomics studies.…”
Section: Copd Gene Expression Studies In Peripheral Bloodmentioning
confidence: 99%
“…Poliska et al found overlapping genes expressed in blood monocyte and alveolar macrophages in a limited number of COPD cases and controls. [70] Bhattacharya et al compared peripheral blood mononuclear cell expression profiles to their previous study of lung tissue,[16] finding several genes with similar expression results across the two tissues. [71] The lung-blood expression relationships found in the latter two studies show that peripheral blood can be used for COPD genomics studies.…”
Section: Copd Gene Expression Studies In Peripheral Bloodmentioning
confidence: 99%
“…The rationale for using blood to study COPD is increasing evidence that COPD is a systemic disease [9], with several systemic biomarkers associated with exacerbation of COPD (see [2] and references therein). Several studies of blood from COPD subjects have suggested that there are genomic signatures associated with COPD (see [2, 10, 11] and references therein). These studies were limited in that they were also of small sample size, did not have replications, and tended to examine individual genes in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Many blood gene expression profiling studies have been published for COPD. [12][13][14][15] Smoking is an important driver and confounder of these studies. The studies typically compare the genome-wide expression profiles between COPD cases and smoking controls, and include self-reported smoking status and/ or pack-years as covariates in the analysis.…”
Section: Introductionmentioning
confidence: 99%